2015
DOI: 10.1038/nature14141
|View full text |Cite
|
Sign up to set email alerts
|

X-domain of peptide synthetases recruits oxygenases crucial for glycopeptide biosynthesis

Abstract: Non-ribosomal peptide synthetase (NRPS) mega-enzyme complexes are modular assembly lines that are involved in the biosynthesis of numerous peptide metabolites independently of the ribosome. The multiple interactions between catalytic domains within the NRPS machinery are further complemented by additional interactions with external enzymes, particularly focused on the final peptide maturation process. An important class of NRPS metabolites that require extensive external modification of the NRPS-bound peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
323
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 185 publications
(352 citation statements)
references
References 46 publications
24
323
0
5
Order By: Relevance
“…4,6,7 Fig. 1 GPA cyclisation in vitro is enabled by diastereomerically pure phenylglycine thioester peptides: teicoplanin seq.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…4,6,7 Fig. 1 GPA cyclisation in vitro is enabled by diastereomerically pure phenylglycine thioester peptides: teicoplanin seq.…”
Section: 2mentioning
confidence: 99%
“…We then tested the level of cyclisation seen in these peptides using the proven enzymatic coupling of OxyB van and OxyA tei , 7,[13][14][15]24,25 with the peptides themselves loaded onto a PCP-X di-domain construct excised from the final module of the teicoplanin NRPS machinery. 7 The results of the Oxy-catalysed turnover of peptides 4-5 demonstrated how vital the L-configuration of the C-terminal residue is for effective enzymatic crosslinking. For the racemic peptide 4, monocyclisation was now seriously impaired by the presence of the incorrect peptide diastereomer, which reduced the levels of monocyclisation to below 20% (Table 1).…”
mentioning
confidence: 99%
“…The CYP450 enzymes catalyze oxidative transformation, which contributes to a broad array of biological functions in living organisms, such as activation or inactivation of many endogenous and exogenous bioactive compounds, particularly xenobiotic detoxification, or even modification of nonribosomal peptides (Guengerich 1991;Haslinger et al 2015). CYP enzymes are found in all kingdoms and domains of life (metazoans, plants, fungi, protists, bacteria, and archaea) and even in a virus.…”
Section: Host Genes Targeted By Small Rnasmentioning
confidence: 99%
“…254 The X-domain is also required in the majority of cases to support efficient P450-catalysed crosslinking in vitro, with this requirement strictly enforced for OxyA and OxyE that act aer OxyB. 243,255,256,[258][259][260][261][262][263] Complestatin 264 and kistamicin 265 are structurally similar to GPAs, and also display several oxidative crosslinks whose generation has been ascribed to P450 enzymes, i.e. NRPS-bound modication with X-domain mediated P450 recruitment.…”
mentioning
confidence: 99%
“…[250][251][252] More recent work has shown that the process of P450 recruitment to the NRPS-bound peptide is more complicated than is the case for PCP-bound amino acids, with GPA biosynthesis relying on the X-domain, a conserved (albeit modied) condensation domain found between the PCP 253 and TE-domains in the nal NRPS module. 243,[254][255][256][257] The X-domain has an interaction interface that specically binds to the Oxy enzymes, with these continually binding to and releasing from the X-domain to ensure that complete crosslinking of the peptide occurs. 254 The X-domain is also required in the majority of cases to support efficient P450-catalysed crosslinking in vitro, with this requirement strictly enforced for OxyA and OxyE that act aer OxyB.…”
mentioning
confidence: 99%